2014
DOI: 10.1111/mec.12728
|View full text |Cite
|
Sign up to set email alerts
|

Phylodynamics of vampire bat‐transmitted rabies in Argentina

Abstract: Common vampire bat populations distributed from Mexico to Argentina are important rabies reservoir hosts in Latin America. The aim of this work was to analyse the population structure of the rabies virus (RABV) variants associated with vampire bats in the Americas and to study their phylodynamic pattern within Argentina. The phylogenetic analysis based on all available vampire bat-related N gene sequences showed both a geographical and a temporal structure. The two largest groups of RABV variants from Argentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 40 publications
0
29
0
3
Order By: Relevance
“…We sequenced the complete nucleoprotein (N) gene from 264 rabies isolates collected from Peruvian livestock between 1997 and 2012 and compared these to representative sequences from throughout the Americas. Because livestock infect neither each other nor bats, each isolate represents a single transmission event from bat to livestock, providing a window of insight into locally circulating bat viruses (14,15). A maximum likelihood (ML) phylogenetic tree revealed three viral lineages in Peru, each of which shared a most recent common ancestor (MRCA) with viruses from other South American countries, consistent with multiple, independent introductions of VBRV into Peruvian bats (Fig.…”
Section: Significancementioning
confidence: 92%
See 1 more Smart Citation
“…We sequenced the complete nucleoprotein (N) gene from 264 rabies isolates collected from Peruvian livestock between 1997 and 2012 and compared these to representative sequences from throughout the Americas. Because livestock infect neither each other nor bats, each isolate represents a single transmission event from bat to livestock, providing a window of insight into locally circulating bat viruses (14,15). A maximum likelihood (ML) phylogenetic tree revealed three viral lineages in Peru, each of which shared a most recent common ancestor (MRCA) with viruses from other South American countries, consistent with multiple, independent introductions of VBRV into Peruvian bats (Fig.…”
Section: Significancementioning
confidence: 92%
“…Prior population genetic studies concluded that the low vagility and small home range sizes of vampire bats generate high genetic differentiation among populations (12,13). However, genetic lineages of VBRV are geographically widespread, implying that the virus overcomes the genetic isolation of its host through a currently unidentified dispersal mechanism (14,15). In carnivores, nonresident, nomadic individuals and seasonal variation in contact networks are thought to influence pathogen prevalence within populations, but the role of host social structure on pathogen spread at larger spatial scales is less understood (16,17).…”
Section: Significancementioning
confidence: 99%
“…While the first analysis consists of testing the impact of environmental factors on dispersal velocity, we have also used a new approach that aims at testing the impact of such factors on the dispersal direction, that Note: For each statistic, we report both the median value and 95% HPD interval. In addition to the Iranian RABV data set introduced in the present study, we also report dispersal statistics estimated for several previously published RABV data sets: bat RABV data sets from Argentina (Torres et al, 2014), Brazil (Vieira, Pereira, Carnieli, Tavares, & Kotait, 2013) and Peru (Streicker et al, 2016), raccoon and skunk RABV data sets from North America Kuzmina et al, 2013) and a dog RABV data set from northern Africa (Talbi et al, 2010). "n" indicates the number of sequences in each data set.…”
Section: Impact Of Environmental Factors On Viral Lineage Dispersalmentioning
confidence: 99%
“…The burden of vampire bat rabies is significant, with an estimated cost of US$50 million per year in livestock losses (Belotto, Leanes, Schneider, Tamayo, & Correa, 2005) and with an estimated force of infection of up to 960 rabies cases per 100,000 inhabitants in a hypothetical outbreak (Schneider et al, 1996). Demographic and ecological factors driving viral dispersal in vampire bats have been investigated specifically for rabies virus de Thoisy et al, 2016;Torres et al, 2014) but such questions have not yet been examined at the level of viral communities.…”
Section: Introductionmentioning
confidence: 99%